John Constantine, Hellblazer. [06], Bloodlines - Ennis, Garth (DC Comics/Vertigo, 2013)
After saving the world a few times, and beating the Devil and lung cancer in one go, John Constantine, the world's greatest magician, is finally starting to feel ahead of the game. Especially with the reappearance in his life of a woman named Kit Ryan. Now, between investigations of a grisly serial murderer and strategies against the Lord of Hell, there's time for a proper booze-up and a few days to recover. But it's too good to last.